LOS IMPOSTORES: reflexiones sobre un conflicto socioambiental - Canchumanya Álvarez, Gianfranco (2020)
In an imperfect environment not all the decisions a player chooses are the best ones, even less if these decisions must take place in a conflict, and in fact, the tension increases and becomes more serious if the benefit of a community, a company and, above all, the State depends on them. It is against this background that this text formulates a reflection on the decisions of the actors involved, drawing on concepts such as game theory, ash equilibrium, transaction costs, the problem of agency, opportunism and, as an added value, conflict management. All these concepts are interwoven throughout the narrative structure, snaking through its four divisions. This segmentation serves the purpose of bringing the reader closer to the nature of the problem. Therefore, in Introduction to the Game, a historical reflection is provided; in Contextualization of the Game, the conflict between the Chinese company MMG Las Bambas and the surrounding communities is narrated; in Final Decision: Nash’s Balance, strategies are evaluated and conflict management is proposed as an essential tool in this type of situation; and, finally, in Final Notes, the importance of choosing the means rather than the end itself is highlighted. In short, this text encourages reflection on actions with the aim of reaching a balance in which all those involved achieve their own benefit without harming that of the other.